Conocimientos y prácticas de prevención en ITS/VIH sida en estudiantes de octavo a decimo año de educación basica del Colegio Nacional Adolfo Valarezo seccion matutina, durante el periodo septiembre 2009- febrero 2010 - Cuenca Carrión, Rosario Lourdes (2010)
It exists a group of factors that you/they place the adolescents in a dangerous situation with regard to the included Infections of Sexual Transmission the HIV-AIDS, among the most important we have: the characteristics characteristic of the stage like the rebelliousness, biological and social physiologic aspects, lack of information about the different transferable illnesses sexually; ignorance and indifference on the infection forms and prevention; besides diverse based myths. The present Investigation understands to study of Traverse Descriptive type that had ace objective to Determines the knowledge and practical preventive on ITS-VIH/SIDA that have those / ace students of the National College Adolfo Valarezo of the City of Loja, during the period September/2009-February/2010. Of the 609 students of Eighth to Tenth year of Basic Education a sample of 372 students was Obtained which are applied a survey of 7 questions; you Also interviews the Rector and the educational ones of the Department of Vocational Orientation of this Institution with the purpose of knowing its participation on the preventive measures of ITS/VIH-AIDS. After this you proceeded to carry out the delivery a student guide and videos as Bibliographical support for the education of adolescent los/las of the Institution in study having as purpose the invigoration of knowledge on forms of prevention of these pathologies. In the Obtained Results we can evidence that los/as students possesses general knowledge on ITS/VIH-AIDS. En una de las conclusiones se llegó a comprobar que la forma de prevención más conocida por los/as jóvenes es el uso del preservativo, por todo lo antes enunciado se cree que la población joven esta en mayor riesgo de ser afectada por la gran variedad de ITS incluido el VIH-SIDA.